2010
DOI: 10.19030/tlc.v7i6.127
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Satisfaction In Higher Education: A TQM Approach

Abstract: This paper was aimed to investigate the levels of satisfaction among faculty members in higher education in Pakistan. Five hundred faculty members were surveyed from leading public and private universities through an instrument developed by the authors and 450 were completed and returned. Percentage method was used to analyze and interpret data. The results highlighted the value of the survey as a strategy for management and human resource planning in universities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It was further supported by the study of Quraishi, Hussain & Rahman (2010) showed the compensation and benefit schemes have connected with job satisfaction.…”
Section: Significant Relation Between Emotional Intelligence Leadersmentioning
confidence: 84%
“…It was further supported by the study of Quraishi, Hussain & Rahman (2010) showed the compensation and benefit schemes have connected with job satisfaction.…”
Section: Significant Relation Between Emotional Intelligence Leadersmentioning
confidence: 84%
“…The work of Gmelchand colleagues has advocated the need for chairs to be developed and mentored, themselves. 35,36 It is understood that each individual faculty case of being unproductive, or especially deleterious, might involve cases of confidentiality; however, department chairs and other administrators can make expectations for productivity and collegial behaviors to faculty and the broader remedies sought by the institution when faculty are not meeting these expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Postema and Markham (2018) indicated dimensions of students' perceived service quality such as teaching quality, student advising, tuition costs, financial assistance, facilities, and curriculum. On the other hand, other dimensions of students' perception of service quality in HEIs include eight factors such as access to Int J Edu Sci, 32(1-3): 1-11 (2021) education-related services, university reputation, training program issues, industry links, understandings of staff, and other non-academic aspects (Appleton-Knapp and Kentler 2016; Hoang et al 2018;Quraishi et al 2017;Wang and Tseng 2012). In the study relating to the significance of students' perceptions, Zineldin (2017) noted that the measurement of students' perceptions about the quality of education service offered by an HEI could reflect the level of students' overall satisfaction on their HEI.…”
Section: Introductionmentioning
confidence: 99%